L’autonomie journalistique et ses limites : enquête pancanadienne auprès d’anciens praticiens - Simon Thibault; Colette Brin; Virginie Hébert; Frédérick Bastien; Tania Gosselin (Communiquer)
Research on journalistic autonomy, particularly through surveys of journalists, has generated interests in recent years. In Canada, the few polls conducted on the subject reveal the positive perceptions of Canadian journalists regarding their professional autonomy. However, the work of researchers has, for decades, exposed the multiple pressures that could affect this autonomy. How do we explain this apparent contradiction? Do these surveys allow us to grasp the nuances of the mechanisms likely to limit journalistic autonomy? The objective of this qualitative investigation is to shed new light on these questions in a pan-Canadian context. Inspired by Reich and Hanitzsch’s (2013) conceptualization of the types of influences on journalistic autonomy, this research suggests that constraints of a political, economic, organizational, procedural and professional nature affect the autonomy of Canadian journalists. It also reveals that self-censorship is a reality that many participants of this research had to contend with, particularly in New Brunswick.